To solve the system of equations, we have the following two equations:
- \( y = -3x + 4 \)
- \( y + 3x = -4 \)
We can use substitution or elimination. Here, we'll use substitution since the first equation gives us \( y \) in terms of \( x \).
-
From the first equation, we have: \[ y = -3x + 4 \]
-
Substitute \( y \) from the first equation into the second equation: \[ (-3x + 4) + 3x = -4 \]
-
Simplifying the left side: \[ -3x + 4 + 3x = -4 \] \[ 4 = -4 \]
This statement \( 4 = -4 \) is a contradiction, meaning that there are no values of \( x \) and \( y \) that satisfy both equations simultaneously.
Thus, the system of equations is inconsistent and has no solution.